Hej!
8(2x - 1) = 16
16x - 8 = 16
16x = 16 + 8
16x = 24 / : 16
x = 24/16 = 1,5
3(y + 6) = 3
3y + 18 = 3
3y = 3 - 18
3y = -15 / : 3
y = -5
2(2x - 1) = 4(x + 1)
4x - 2 = 4x + 4
4x - 4x = 4 + 2
0 = 6
Równanie sprzeczne, nie posiada rozwiązań w zbiorze liczb rzeczywistych.
2(3 - x) = 10
6 - 2x = 10
-2x = 10 - 6
-2x = 4 / : (-2)
x = -2
2(3x + 5) = 4
6x + 10 = 4
6x = 4 - 10
6x = -6 / : 6
x = -1
3(y + 6) = 3(2 + y)
3y + 18 = 6 + 3y
3y - 3y = 6 - 18
0 = -12
Równanie sprzeczne, nie posiada rozwiązań w zbiorze liczb rzeczywistych.
6(5x + 2) = 6(x - 1)
30x + 12 = 6x - 6
30x - 6x = -6 - 12
24x = -18 / : 24
x = -18/24 = -3/4
Pozdrawiam! - Julka